Implementing and investigating distributed leadership in a national university network – SaMnet. Issue 2 (4th March 2017) - Sharma, Manjula D.; Rifkin, Will; Tzioumis, Vicky; Hill, Matthew; Johnson, Elizabeth; Varsavsky, Cristina; Jones, Susan; Beames, Stephanie; Crampton, Andrea; Zadnik, Marjan; Pyke, Simon
ABSTRACT: The literature suggests that collaborative approaches to leadership, such as distributed leadership, are essential for supporting educational innovators in leading change in teaching in universities. This paper briefly describes the array of activities, processes and resources to support distributed leadership in the implementation of a network, the Science and Mathematics Network of Australian University Educators – SaMnet. The research study investigated participating educational innovators' experiences of distributed leadership using a mixed method approach after 2 years of immersion in SaMnet. Fifty innovators from 100 were surveyed and data analysed to obtain influences of the teams, the institution and SaMnet. Focus groups were used to extract rich descriptions of the experiences of the innovators. The study suggests that distributed leadership as the approach underpinning SaMnet cultivated leadership helping to complement team and institutional influences in a measurable way and to support educational innovators in leading change in university science and mathematics teaching.